Studying a Study and Testing a Test : How to Read the Medical Evidence. - Riegelman, Richard K. (Wolters Kluwer Health, 2004)
Now in its Fifth Edition, this best-selling text presents a step-by-step approach to critical and efficient reading of the medical literature. Health care professionals will learn how to evaluate clinical studies, identify flaws in study design, interpret statistics, and apply evidence from clinical research in practice. This edition's new section, Guide to the Guidelines, reflects the growing use and importance of clinical guidelines. The outcomes research chapter includes concepts of safety and effects of interactions on outcomes. This edition also presents statistics more graphically. Uniqu.